Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s13277-014-2516-6
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic and prognostic value of circulating miR-18a in the plasma of patients with gastric cancer

Abstract: The aim of this manuscript is to analyze the diagnostic and prognostic value of circulating miR-18a in the plasma of patients with gastric cancer. In this study, 82 patients with gastric cancer and 65 healthy controls were enrolled in the study, and 10 ml of peripheral venous blood was collected for RNA extraction. miR-18a expression was determined using TaqMan quantitative real-time polymerase chain reaction assay and was further correlated with patients' clinicopathological parameters and the follow-up data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Similarly, miR-183, a cluster (miR-96 and miR-182) of family genes, which is a potent prognostic marker for lung adenocarcinoma and other cancers, was found to be highly upregulated in our TNBC samples 21-27. Likewise, a well-known onco-miR miR-18a belongs to miR-17-92 cluster that consists of seven miRNAs (miR-17-5p, miR-17-3p, miR-18a, miR-19b, miR-20a and miR-92) 28 and is considered as a biomarker for several cancers, particularly, esophageal, nasopharyngeal, colorectal and gastric cancer 29-34. Another miR that was highly dysregulated in TNBC samples was miR-96.…”
Section: Resultsmentioning
confidence: 72%
“…Similarly, miR-183, a cluster (miR-96 and miR-182) of family genes, which is a potent prognostic marker for lung adenocarcinoma and other cancers, was found to be highly upregulated in our TNBC samples 21-27. Likewise, a well-known onco-miR miR-18a belongs to miR-17-92 cluster that consists of seven miRNAs (miR-17-5p, miR-17-3p, miR-18a, miR-19b, miR-20a and miR-92) 28 and is considered as a biomarker for several cancers, particularly, esophageal, nasopharyngeal, colorectal and gastric cancer 29-34. Another miR that was highly dysregulated in TNBC samples was miR-96.…”
Section: Resultsmentioning
confidence: 72%
“…A thorough review of literature on the diagnostic accuracy of miRNA biomarkers for gastric cancer revealed that miR-18a and miR-21 are among the leading candidates that deserve further interrogation and validation (34,35). Comprehensive RNA sequencing on 20 gastric cancers and healthy controls revealed a panel of miRNAs (miR-1, miR-20a, miR-27a, miR-34, and miR-423-5p) that can differentiate patients with gastric cancer from healthy controls (36).…”
Section: Liquid Biopsies: Novel Frontiers In Cancer Diagnosismentioning
confidence: 99%
“…Meanwhile, the role of miR-18a in cancer development remains elusive. Several studies have observed that miR-18a is highly expressed in several types of cancer, including nasopharyngeal carcinoma (10), and prostate (11) and gastric (12,13) cancer. The miRNA promotes cancer development via inducing proliferation and inhibiting apoptosis.…”
Section: Introductionmentioning
confidence: 99%